Penerapan Pembinaan CLCK (Contoh, Latihan, Control, Kerja Mandiri) untuk Meningkatkan Kompetensi Guru dalam Menyusun RPP di SD Negeri 3 Banyuringin - Eni Nur Istiana (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
Referring to the results of academic supervision of teacher competence in preparing lesson plans at SD Negeri 3 Banyuringin in semester 1 of the 2022/2023 school year, it shows that the average value of teacher competency in preparing lesson plans is still low and not as expected. This needs to be followed up immediately and a solution to the teacher's problem is sought. With the various problems faced by each teacher in managing learning, the researcher as the Principal discussed with colleagues (Dabin Supervisor) and planned to carry out CLCK coaching (Example, Exercise, Control, Independent Work) preparation of lesson plans and present the results obtained in reports School Action Research. The formulation of the problems in the research are: 1) Can CLCK coaching (Example, Exercise, Control, Independent Work) increase teacher competence in preparing lesson plans at SD Negeri 3 Banyuringin, Singorojo District, Kendal Regency Semester 2 for the 2022/2023 Academic Year?, 2) How much a large increase in teacher competence in preparing lesson plans through CLCK coaching (Examples, Training, Control, Independent Work) at SD Negeri 3 Banyuringin, Singorojo District, Kendal Regency Semester 2 of the 2022/2023 Academic Year?. It is hoped that after participating in these coaching activities, the competence of teachers in preparing lesson plans will increase. School Action Research was carried out in 2 cycles, where each cycle consisted of 3 meetings. Subjects in the study included: class I-VI teachers, PJOK teachers, and PAIdBP teachers at SD Negeri 3 Banyuringin Semester 2 Academic Year 2022/2023. The process of implementing CLCK coaching (Example, Training, Control, Independent Work) was carried out in research through three phases, namely: planning, implementation process and evaluation. The results of the study show that the teacher's competence in preparing lesson plans has increased in each cycle. This is evidenced by the acquisition of the average teacher competency score in preparing lesson plans. The average acquisition of teacher competence in the initial conditions the average value of teacher competence in preparing lesson plans reached 52.89, cycle I rose to 73.43 (increased by 20.54) and at the end of cycle II to 89.50 (increased of 16.07). Based on the results of the study, it can be concluded that the application of CLCK coaching (Example, Training, Control, Independent Work) can improve teacher competence in preparing lesson plans at SD Negeri 3 Banyuringin Semester 2 Academic Year 2022/2023. It is hoped that the Principal will always forge himself and improve his competence in providing direction and guidance to teachers in schools so that they can achieve the expected educational goals.